Assessing vulnerability to climate change in smallholder irrigation schemes of Zimbabwe - Mwadzingeni, Liboster; Mugandani, Raymond; Mafongoya, Paramu L. (MDPI, 2021)
Globally, climate change poses enormous threats to the livelihoods of rural communities in arid and semi-arid regions. Assessing the extent of vulnerability is critical to identify climate hot spots and develop appropriate adaptation policies and strategies. This paper uses the Livelihood Vulnerability Index (LVI) and the Livelihood Vulnerability Index—Intergovernmental Panel on Climate Change (LVI-IPCC) to compare vulnerability to climate change in the Exchange, Insukamini, and Ruchanyu smallholder irrigation schemes (SISs) in the Midlands Province of Zimbabwe. A questionnaire was used to collect data from a sample of 317 randomly selected households. Results show higher exposure and sensitivity to climate change in the Insukamini irrigation scheme despite the higher adaptive capacity. Both LVI and LVI-IPCC show that households in Insukamini irrigation scheme are more vulnerable to climate change than in Exchange and Ruchanyu irrigation schemes, attributed to water insecurity, poor social networks, and natural disasters and climate variability. The study recommends that development and investment in Insukamini and Ruchanyu should prioritize improving social networks while Exchange should primarily focus on improving livelihood strategies. Using the LVI-IPCC framework is a key methodology for understanding the vulnerability of communities in SISs and identifying areas that need prime development and investment. These results have implications on implementing investments and livelihood policies in SISs of Zimbabwe.